2018
DOI: 10.1111/jcmm.13843
|View full text |Cite
|
Sign up to set email alerts
|

Timing of erythropoietin modified mesenchymal stromal cell transplantation for the treatment of experimental bronchopulmonary dysplasia

Abstract: The aim of this study is to optimize the timing of erythropoietin gene modified mesenchymal stem cells (EPO‐MSCs) transplantation for bronchopulmonary dysplasia (BPD). Three weeks post‐operation, the results indicated that the damage of airway structure and apoptosis were significantly decreased, the proliferation was increased in three EPO‐MSCs transplantation groups as compared with BPD mice. Moreover, the inflammation cytokines were improvement in early EPO‐MSCs injection mice than in BPD mice, but there wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 14 publications
2
6
0
Order By: Relevance
“…Our results also showed that in the umbilical cord tissue homogenates, the activation of MAPK pathway is higher in neonates with BPD compared to healthy controls. These findings corroborate a previous study showing that the early versus late transplantation of erythropoietin gene‐modified stem cells (EPO mesenchymal stem cells) might mitigate BPD injury by inhibiting the inflammatory response through the downregulation of p38/MAPK pathway 22 . Our study also suggests that there is a possible link between BPD and HTLV‐1 infection.…”
Section: Discussionsupporting
confidence: 92%
“…Our results also showed that in the umbilical cord tissue homogenates, the activation of MAPK pathway is higher in neonates with BPD compared to healthy controls. These findings corroborate a previous study showing that the early versus late transplantation of erythropoietin gene‐modified stem cells (EPO mesenchymal stem cells) might mitigate BPD injury by inhibiting the inflammatory response through the downregulation of p38/MAPK pathway 22 . Our study also suggests that there is a possible link between BPD and HTLV‐1 infection.…”
Section: Discussionsupporting
confidence: 92%
“…These findings indicated that two peptides may play an antiinflammatory role in the process of BPD. And previous studies have shown that the regulation of inflammation-related signal pathways such as p38 mitogen activated protein kinases (p38MAPK) signal pathways and nuclear factor-κB (NF-κB) signal pathway can reduce the level of pro-inflammatory cytokines, thus relieving the pulmonary inflammation of BPD [ 76 , 77 ]. Combined with previous studies, we consider that the two peptides secreted from hUC-MSCs may decrease the production of pro-inflammatory cytokines through inflammation-related signal pathways and further researches need to be conducted to validate the possible pathway.…”
Section: Discussionmentioning
confidence: 99%
“…These ndings indicated that two peptides may play an anti-in ammatory role in the process of BPD. And previous studies have shown that the regulation of in ammation-related signal pathways such as p38 mitogen activated protein kinases (p38MAPK) signal pathways and nuclear factor-κB (NF-κB) signal pathway can reduce the level of pro-in ammatory cytokines, thus relieving the pulmonary in ammation of BPD [78,79].…”
Section: Discussionmentioning
confidence: 99%